Corelation Of Nutrient State and immunization With Incident Of Acute Respiratory Tract Infection Toward Children Under 5 Years Old in Mabelopura Publik Healt Centre (PHC) - Hutagaol, Iin Octaviana; Lamidji, Misnawati (Infokes, 2019)
Acute Respiratory Tract Infection (ARTI) most common in children under 5 year old. And it could lead death due to attack one of respiratory tract from nose to alveoli. Increasingof ARTI prevalensi influenced by same factors. Such as environment (air polition), individual factor (age, Weight birth, nutrient state and immunization)  family factor. The aim of this research to obtain the correlation of nutrient state and immunization with incident of ARTI toward childrent under 5 years old in Mabelopura PHC. This is analytical research by using cross sectional approaching. The population wera those children under 5 years old who visited Mabelopura PHC and with ARTI diagnosed. Total samples were 43 resppondents and taken by accidental sampling technique. Data analsed by Chi-Square test. The  result shown that most of children have poor nutrient state category (79,1%), incomplete immunization (62,8%), and in suffering of ARTI (65,1%). Conelusion it have correlation between nutrient state and immunization with incident of ARTI  childrent under 5 years old in Mabelopura PHC. Expectation of this research could become one of reference for mabelopura PHC administration in performing of healt promotion toward community about nutrient, immunization and ARTI.